2020
DOI: 10.3390/met10020190
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Laser Deposition of Fe-Based Metallic Powder under Cryogenic Conditions

Abstract: The purpose of this study was to demonstrate the novel technique of laser deposition of Fe-based powder under cryogenic conditions provided by a liquid nitrogen bath. Comparative clad layers were produced by conventional laser cladding at free cooling conditions in ambient air and by the developed process combining laser cladding and laser gas nitriding (hybrid) under cryogenic conditions. The influence of process parameters and cooling conditions on the geometry, microstructure, and hardness profiles of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
(52 reference statements)
0
13
1
Order By: Relevance
“…The highest HV10 values were measured in the HAZ, whose structures were identified as brittle bainitic and martensitic structure. Lisiecki and Ślizak [57] stated, that high hardness of welded layers was caused by a high cooling rate during welding process. The significant effect of in situ local heat treatment was observed for Specimen 5, modified by two additional stitches.…”
Section: Hardness Hv10 Measurementsmentioning
confidence: 99%
“…The highest HV10 values were measured in the HAZ, whose structures were identified as brittle bainitic and martensitic structure. Lisiecki and Ślizak [57] stated, that high hardness of welded layers was caused by a high cooling rate during welding process. The significant effect of in situ local heat treatment was observed for Specimen 5, modified by two additional stitches.…”
Section: Hardness Hv10 Measurementsmentioning
confidence: 99%
“…Laser cladding offers some advantages over the other methods of cladding or coatings [1][2][3][4][5][6][7][8][9][10]. The most significant advantages are high power density, localized and precise heating, high scanning speed, thus low heat input, low penetration depth and low dilution.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid nitrogen bath providing cryogenic conditions of cooling was also tested by some researchers during laser surface melting or heat treatment, mainly for nonferrous alloys [18][19][20][21][22][23]. Such technique of liquid nitrogen bath cooling of the substrate was adopted and developed by the authors for laser powder deposition of metallic and composite coatings, as demonstrated in several previous publications [1,[24][25][26][27][28][29][30][31]. It is worth to note, that complexity and difficulty of the laser powder deposition under such cryogenic conditions with coaxial powder delivery into the melt pool is significantly higher than the laser surface melting of the substrate supercooled by liquid nitrogen bath.…”
Section: Introductionmentioning
confidence: 99%
“…To study the effect of ultrasonic on the welded bead geometry, the penetration depth, the area of the fusion zone, and the clad layer were measured, as shown in Figure 3. The value of weld dilution rate "D" was calculated by the following formula [28]:…”
Section: Introductionmentioning
confidence: 99%
“…The observations of fracture surfaces, after the tensile test and Charpy impact test, were completed using a scanning electron microscope (MERLIN Compact, Carl Zeiss, Oberkochen, Germany). The value of weld dilution rate "D" was calculated by the following formula [28]:…”
Section: Introductionmentioning
confidence: 99%